Investigation of the effects of pulse width modulation on the laser sintering of LATP for all-solid-state batteries - Wehbe, H.; Schmidt, L. O.; Kandula, M. W.; Dilger, K. (Applied physics. A, Materials science & processing, 2022)
Inorganic solid electrolytes are the most important component for realizing all-solid-state batteries with lithium metal anodes and enable safe battery cells with high energy densities. Their synthesis and processing are the subject of current research, especially the NASICON-type Li 1+x AlxTi 2-x (PO 4 ) 3 (LATP). Herein, the ability of sintering with electro-magnetic irradiation is investigated and correlated with different properties of prepared LATP pellets. First of all, an infrared camera records the temperature of the surface during the treatment. Second, the effect of the pulse fluence is investigated in terms of the topology and morphology of the pellets. Here, the arithmetic surface roughness Ra is the main parameter. Then, the depth of the radiation interaction in the pellet is measured. The focus of this paper is on the different pulse widths of the laser sources, and therefore, similar pulse and hatch overlap ensure equivalent areal energy input in both cases. As a summarized result, treatment with a shorter pulse width generates high peak pulse powers, resulting in higher temperatures, rougher surfaces and affecting deeper layers of the pellets compared to treatment with longer pulse width. On the contrary, excessive power leads to the ablation of the material up to destruction.